2003
DOI: 10.1038/sj.hdy.6800249
|View full text |Cite
|
Sign up to set email alerts
|

Rapid response to artificial selection on flower size in Phlox

Abstract: Quantitative characters are often said to evolve rather slowly, taking many generations to exhibit appreciable differences among populations. We tested this notion experimentally by performing bi-directional selection on corolla diameter of plants from a wild population of Phlox drummondii for three generations. By monitoring flower size, tube length and stigma-anther proximity of flowers, we obtained the direct and indirect responses to selection, and calculated genetic correlations, realized and narrow sense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 41 publications
7
24
0
Order By: Relevance
“…This 'selfing syndrome' has been observed frequently in populations with increased selfing rates (Goodwillie et al, 2010), and can evidently evolve rapidly (Bodbyl Roels andKelly, 2011). Bodbyl Roels andKelly (2011) prevented pollinators from accessing flowers in experimental populations of the SC plant Mimulus guttatus and observed reduced anther-stigma separation in only five generations, and several studies have shown similarly rapid changes in floral size in response to artificial selection (Worley and Barrett, 2000;Lendvai and Levin, 2003;Delph et al, 2004). Given the rapidity of such responses, we should perhaps not be surprised that a selfing syndrome was able to evolve following the loss of SI in the selfing species Capsella rubella over several thousand generations (Foxe et al, 2009;Slotte et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This 'selfing syndrome' has been observed frequently in populations with increased selfing rates (Goodwillie et al, 2010), and can evidently evolve rapidly (Bodbyl Roels andKelly, 2011). Bodbyl Roels andKelly (2011) prevented pollinators from accessing flowers in experimental populations of the SC plant Mimulus guttatus and observed reduced anther-stigma separation in only five generations, and several studies have shown similarly rapid changes in floral size in response to artificial selection (Worley and Barrett, 2000;Lendvai and Levin, 2003;Delph et al, 2004). Given the rapidity of such responses, we should perhaps not be surprised that a selfing syndrome was able to evolve following the loss of SI in the selfing species Capsella rubella over several thousand generations (Foxe et al, 2009;Slotte et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Despite apparently overwhelming directional selection for larger flowers, populations retain high genetic variation in flower size. Artificial selection can greatly increase mean flower size (Worley & Barrett 2000;Lendvai & Levin 2003;Delph et al 2004;Lehtila & Brann 2007;Kelly 2008), indicating that natural populations are not at maximum values for this trait.…”
Section: Introductionmentioning
confidence: 99%
“…This greatly depends upon the scale of observation: small genotypic changes can accumulate quite rapidly, allowing for the development of disease resistant microbes (Holden et al 2004) and artificial selection of domestic species has shown that dramatic phenotypic changes can accumulate within the space of a few generations (Lendvai and Levin 2003). Neither of these, however, may be directly comparable to the natural selection pressures affecting ecologically significant traits of colonizing species, which are concomitantly interacting with other evolving species.…”
Section: Group B: Changementioning
confidence: 98%